2011
DOI: 10.1002/jbm.b.31925
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous titanium dioxide coating for metallic implants

Abstract: A bioactive mesoporous titanium dioxide (MT) coating for surface drug delivery has been investigated to develop a multifunctional implant coating, offering quick bone bonding and biological stability. An evaporation induced self-assembly (EISA) method was used to prepare a mesoporous titanium dioxide coating of the anatase phase with BET surface area of 172 m(2)/g and average pore diameter of 4.3 nm. Adhesion tests using the scratch method and an in situ screw-in/screw-out technique confirm that the MT coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 40 publications
0
36
1
Order By: Relevance
“…In a previous study, we analyzed the cellular response of osteoblasts (human fetal osteoblasts) to mesoporous TiO 2 coatings generated by the evaporation-induced self-assembly method (EISA) [25,26] and chemically modified with magnesium [27]. We demonstrated that human fetal osteoblasts (hFOB) adhesion was significantly enhanced by the presence of the mesopores.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we analyzed the cellular response of osteoblasts (human fetal osteoblasts) to mesoporous TiO 2 coatings generated by the evaporation-induced self-assembly method (EISA) [25,26] and chemically modified with magnesium [27]. We demonstrated that human fetal osteoblasts (hFOB) adhesion was significantly enhanced by the presence of the mesopores.…”
Section: Introductionmentioning
confidence: 99%
“…The application of a titanium oxide coating on implants is based on pore morphology, with calcium, silicon, phosphorus, and silver particle enrichment. 62 The coating inhibits the adhesion and growth of bacteria such as Streptococcus mutans, Streptococcus epidermis, and E. coli and prevents the occurrence of inflammation around the implants. Preliminary biological characterization also indicated that a nanocoating can improve the adhesion and proliferation of osteoblast cell lines.…”
mentioning
confidence: 99%
“…Fig. 1 Films generated by sol-gel methods in (A) [15] and (B) [16] Oxidation that coats a bioactive TiO 2 layer on the Ti substrate is a promising approach to medical applications. With a mesoporous bioactive TiO 2 layer, the coating improves the accumulation of Ca and P, which subsequently transfer to hydroxyapatite [17,18].…”
Section: Physicochemical Methodsmentioning
confidence: 99%